Filarioid infections in wild carnivores: a multispecies survey in Romania - Angela Monica Ionică; Ioana Adriana Matei; Gianluca D’Amico; Jana Ababii; Aikaterini Alexandra Daskalaki; Attila D. Sándor; Dorin Valter Enache; Călin Mircea Gherman; Andrei Daniel Mihalca (Parasites & Vectors, 2017)
Abstract Background Filarioids are vector-borne parasitic nematodes of vertebrates. In Europe, eight species of filarioids, including zoonotic species, have been reported mainly in domestic dogs, and occasionally in wild carnivores. In Romania, infections with Dirofilaria spp. and Acanthocheilonema reconditum are endemic in domestic dogs. Despite the abundant populations of wild carnivores in the country, their role in the epidemiology of filarioid parasites remains largely unknown. The aim of the present study was to assess the host range, prevalence and distribution of filarioid infections in wild carnivores present in Romania. Methods Between May 2014 and February 2016, 432 spleen samples originating from 14 species of wild carnivores have been tested for the presence of DNA of three species of filarioids (D. immitis, D. repens and A. reconditum). Results Overall 14 samples (3.24%) were molecularly positive. The most prevalent species was D. immitis (1.62%), accounting for 50% (n = 7) of the positive animals. The prevalence of D. repens was 1.39%, while that of A. reconditum was 0.23%. No co-infections were detected. Dirofilaria immitis DNA was detected in five golden jackals, Canis aureus (7.58%), one red fox, Vulpes vulpes (0.33%), and one wildcat, Felis silvestris (10%). The presence of D. repens DNA was detected in two red foxes (0.66%), two golden jackals (3.03%), one grey wolf (7.14%), and one least weasel, Mustela nivalis (33.33%). Acanthocheilonema reconditum DNA was found only in one red fox (0.33%). Conclusion The present study provides molecular evidence of filarial infections in wild carnivore species in Romania, suggesting their potential epidemiological role and reports a new host species for D. repens.